Influence of pretreatment on surface interaction between Cu and anatase-TiO2 in the simultaneous photoremediation of nitrate and oxalic acid. Issue 2 (April 2019) - Adamu, Haruna; McCue, Alan J.; Taylor, Rebecca S.F.; Manyar, Haresh G.; Anderson, James A.
Graphical abstract: Abstract: Copper-promoted anatase-type TiO2 photocatalysts (2.5 wt% Cu) were prepared by wet impregnation onto TiO2 which was pre-calcined at 600 °C and the other not subjected to any thermal pre-treatment. In the latter case, the material was inactive for the photo-reduction of nitrate whereas 600 °C pre-calcined TiO2 yielded a material which was active for the same reaction. The surface properties of the materials were determined by BET Surface area, SEM TEM, XRD, XPS, TPR, UV–vis diffuse reflectance, DTA, N2 O pulsed chemisorption and FTIR studies. The BET and XRD and DTA showed that pre-calcination of TiO2 stabilised the support, but coalescence of particles was observed in TiO2 that was not subjected to any thermal pre-treatment as evidenced by crystallite growth. Similarly, XPS, FTIR and TPR proved the formation of Cu2 O particles on the surface of pre-calcined TiO2 . On the other hand, the absence of pre-calcination step resulted in interring of Cu species within the grown anatase crystallites that hindered their proper distribution over TiO2, helped in its inactiveness in the photoreduction of nitrate. However, the prepared material using pre-calcined TiO2 showed the overall nitrate and oxalic acid removal efficiency of 31 and 70% with N2 and NH4 + selectivity of 44.9 and 55.1%, respectively. The results provide insight into the significance of activity-structure relation, inferring that the two surfaces were chemically not similar. Thus, as even supported by adsorption experiment, difference in photocatalytic behaviour amongst the prepared materials was a function of crystallinity, particle size, absence of surface defect and high energy sites.